2018
DOI: 10.3390/agriculture8070109
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Household Succession in Agricultural Occupation in Nakhon Ratchasima Province, Thailand

Abstract: This research aims to determine the factors affecting the succession of youths from farming households in agricultural occupations within Nakhon Ratchasima Province, Thailand. Primary information was collected from 400 farm households using a structured questionnaire. Binary logistic regression analysis shows that five variables significantly influence the decision of the new generation on succession in agricultural occupation: Their experience in agricultural work, attitude towards agriculture as an occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…family and peers) and of messages conveyed by the media (Boateng and Löwe, 2018). For instance, in Thailand, many farming parents think that their children will have more opportunities if they get a non-farming job and advise them to avoid becoming farmers (Rayasawath, 2018;Rigg et al, 2012).…”
Section: Approaches To Analyse Young People's Willingness To Farmmentioning
confidence: 99%
“…family and peers) and of messages conveyed by the media (Boateng and Löwe, 2018). For instance, in Thailand, many farming parents think that their children will have more opportunities if they get a non-farming job and advise them to avoid becoming farmers (Rayasawath, 2018;Rigg et al, 2012).…”
Section: Approaches To Analyse Young People's Willingness To Farmmentioning
confidence: 99%
“…Previous studies on the factors that influence the young generation's decisions to pursue a career in agriculture indicated that attitudes and beliefs towards the agricultural profession are one of the most influential factors in whether or not to continue family succession or to enter as new entrants (Ayanda et al, 2012;Bello et al, 2015;Krajangchom et al, 2016;May et al, 2019;Rayasawath, 2018;Shenaifi, 2013;Shireesha et al, 2016). Still, most studies presumed the dimensions of attitude of the young generation, and integrated these dimensions into questionnaires that indicate the agreement or disagreement of the young generation with the stated dimensions.…”
Section: Attitude Towards Agriculture As a Professionmentioning
confidence: 99%
“…Although the achievements of the above programs must be carefully monitored and evaluated, it is equally important to understand the young generation's attitude towards agriculture as a profession. Previous studies indicated the significance of the young generation's attitude as one of the key factors shaping the decisions whether or not to carry on as family successors of a farming business (Ayanda et al, 2012;Bello et al, 2015;Krajangchom et al, 2016;May et al, 2019;Rayasawath, 2018). In many developing countries, the lukewarm and negative attitudes of youth towards agriculture as a profession are a concern and challenge for the future of the agriculture sector (Shireesha et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The variable "remoteness" always has a negative effect on family farm succession (Aldanondo Ochoa et al, 2007;Cavicchioli et al, 2018;Glauben et al, 2004;Kerbler, 2012;Mann, 2007a;Mishra and El-Osta, 2010;Rayasawath, 2018). As such, farms located farther from developed or commercial areas have less propensity to be succeeded.…”
Section: Quantitative Studiesmentioning
confidence: 99%